Penggunaan “Gudang Teks” Sebagai Digitalisasi Teks Negosiasi Berbasis Google Sites dalam Menunjang Pembelajaran Bahasa Indonesia - Khansa Hafidza; Rachel Fatma Maharani Putri; Alvin Demas Arethusa; Sri Hastuti (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
In the current era, digital learning media began to be developed along with the rapid development of information technology. Educators are indirectly required to make adjustments to the development of information technology-based learning media. Gudang Teks is a Indonesian learning media program designed through the world wide web precisely on google-sites which is a place for storage of negotiation text materials. With this, this study was conducted to analyze information technology-based learning media on the use of LMS in the form of google-sites under the name "Text Warehouse" in the negotiation text learning process at the Class X high school level. The research methods used in this study are qualitative descriptive methods based on data analysis and literature studies. The development model used in research uses the type of research and development or Research and Development (R &D) with the 4-D development method developed by S. Thiagarajan and consists of 4 main stages, namely define, design, develop, and disseminate. The Text Warehouse is also analyzed using SWOT analysis in the form of strengths and weaknesses, opportunities, and threats so that they can be further evaluated and considered in their use. The results of the analysis show that the Text Warehouse is quite feasible to be used in the negotiation text learning process, especially in grade X high school students.